Studies on Antioxidant Activity, Total Phenolic Content and Organoleptic Quality of Lime Blended Aloe RTS - Ameda, Swarnalatha; Lakshminarayana, D.; Prashanth, P.; Cheena, J. (International Journal of Bio-resource and Stress Management, 2024)
The present experiment was carried out during the year December, 2020 to April, 2021 as Completely randomised design with factorial concept and conducted at PG laboratory, College of Horticulture, Rajendranagar, Hyderabad, Telangana, (500030), India. To develop a healthy ready to serve drink from Aloe and lime juice, the blend comprising of 90:10 and 85:15 Aloe (Aloe barbadensis) and lime (Citrus aurantifolia), respectively were prepared by addition of two chemical preservatives (KMS 70 ppm and Sodium benzoate 120 ppm) and evaluated for antioxidant activity, total phenols, ascorbic acid content, microbial analysis and organoleptic evaluation for a storage period of three months with 15 days of intervals under ambient and refrigerated storage conditions. There were remarkable changes in the loss of ascorbic acid, total phenol content (folin-ciocalteau method) and antioxidant activities (DPPH) were observed more under ambient storage rather than refrigerated storage during 90 days’ period. Organoleptic evaluation revealed that treatment 90:10 (Aloe: lime)+KMS 70 ppm obtained more acceptability in terms of colour, flavour, taste and overall score among the other treatments. Between the two storage conditions, the changes in the quality characteristics of the RTS (ready to serve) drink were slower in refrigerated storage conditions as compared to ambient conditions. Microbial growth is negligible in refrigerated storage, so it was highly recommended.